Pengaruh Swedish Massage Terhadap Penurunan Tekanan Darah Pada Pasien Hipertensi Di Ruang Rawat Inap RS An-Nisa Tangerang Tahun 2020 - Tri Widyaningrum (Jurnal Health Sains, 2020)
Hypertension can be defined as a persistent blood pressure where the systolic pressure is above 140 mmHg and the diastolic pressure is above 90 mmHg. One of the changes that occurs is the increased blood pressure caused by increased resistance of the peripheral blood vessels, normal systolic approximately 170 mmHg and normal diastolic approximately 90 mmHg. Swedish Massage to lower blood pressure in hypertensive patients Swedish massage is a massage technique that focuses on relaxation and improves blood circulation by engaging the muscles. the use of massage by nurses has the potential to significantly improve health status. The purpose of this study was to determine the effect of Swedish massage on reducing blood pressure in hypertensive patients in the inpatient room of An-Nisa Hospital, Tangerang in 2020. The research method used in this study was a quasi experimental design: one group pre test and post test design. The population in this study amounted to 60 respondents. The technique used for data collection is accidental sampling. Results: Based on the t-paired test that p-value <0.05, it can be stated that Ho is rejected and Ha is accepted, meaning that there is an effect between Swedish massage on reducing blood pressure in hypertensive patients in the inpatient room of An-Nisa Hospital, Tangerang, 2020. Conclusion : there is an effect of Swedish massage on reducing blood pressure in hypertensive patients in the inpatient room of An-Nisa Hospital, Tangerang, 2020.